Studying the User Experience of an Educational AR-Based App for Smart Glasses - Santana, Ronny (2022)
The steady evolution of wearable technology—along with augmented reality (AR)—has enabled important advances in teaching and learning. We present STEM Education, an interactive AR application for smart glasses. We evaluate the app’s user experience (UX) with undergraduate STEM (Science, Technology, Engineering, and Mathematics) students. More specifically, we focus on the students’ overall satisfaction, degree of technological acceptance, mental workload, and emotional response. Our observations suggest that the app improves the student’s learning quality, while promoting high levels of engagement and satisfaction. We discuss these findings and their implications in the design of similar technology for educational contexts.